Taxation and the Tiebout Model: The Differential Effects of Head Taxes, Taxes on Land Rents, and Property Taxes - Mieszkowski, Peter; Zodrow, George R. (Journal of Economic Literature, 1989)
on the theory of state and local public finance is the seminal paper by Charles Tiebout (1956). Tiebout constructed a multijurisdictional model in which independent local governments offer a wide variety of expenditure and tax policies, and perfectly mobile consumers reveal their preferences for local public goods through their choice of residential community. He argued that, under such circumstances, local public service provision would be efficient. The Tiebout model has formed the basis of a vast number of subsequent articles in the state and local public finance literature and has also been very influential in urban and regional economics. The efficiency properties of various Tiebout-type models of local public good provision have been examined, and the role of politics in these models has been debated at length in this literature. Of more direct relevance to this paper, however, is the fact that although Tiebout had little to say directly about taxation (simply assuming the existence of head taxes), subsequent analyses have used adaptations of this model to examine the effects of local head taxes, land taxes, and property taxes. It is the literature on the efficiency and distributional effects of alternative local taxes that is the subject of this survey. 1